PERAN POSYANDU DALAM PENINGKATAN STATUS GIZI BALITA DI NAGARI SARIK ALAHAN TIGO KAB SOLOK - Nilda Elfemi; Yuhelna, Yuhelna; Sarbaitinil, Sarbaitinil; Isnaini, Isnaini; Yanti Sri Wahyuni; Hefni, Hefni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
One of the public health service providers that directly impacts the community is the Integrated Health Post (Posyandu). Posyandu is a form of Community-Based Health Effort (UKBM) implemented by the government and the community to empower and facilitate access to health services for mothers, infants, and toddlers. Posyandu is the spearhead of health services, aiming to accelerate efforts to reduce infant and maternal mortality rates. Posyandus carry out various activities, including monitoring toddler growth and development, health services, maternal and child services, including immunizations for disease prevention, diarrhea management, family planning services, counseling, and counseling/referrals when needed.